Bridging the gender gap: Investigating disparities in student communication skills in the digital education era - Adelia Alfama Zamista; Khairul Azmi; Saifaldin Idris Onia (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2024)
The communication gap between male and female students remains a subject of debate. In the digital education era, it is necessary to examine whether gender differences truly influence communication skills or whether other factors play a more dominant role. This study examines students’ communication skills by gender, identifying similarities and differences across language use, interpersonal abilities, communication ethics, and technology utilization in the learning process. This study employed a comparative descriptive method with a sample of 38 students selected through quota sampling. Data were collected using a questionnaire, analyzed with SPSS, and tested using an independent samples t-test, with assumptions of normality and homogeneity of variance being assessed. The study findings reveal: (1) female students demonstrate higher levels of communication skills in language use, listening ability, and logical thinking, whereas male students perform better in communication ethics and technology utilization; multilingual communication remains the main weakness for both groups. (2) Gender-based communication skill scores show a very small difference between females (3.32%) and males (3.28%), with a minimal gap of 0.04, confirming that there is no statistically significant difference. The study concludes that there is no significant difference in communication skills between genders, thereby rejecting biological determinism. Multilingual communication is a shared weakness, accompanied by dependence on digital translation tools. This study contributes to supporting the social construction of gender, rejecting biological determinism, and demonstrating that an equal educational environment and student-centered learning are effective in neutralizing communication bias.